2018
DOI: 10.1021/acs.orglett.8b01888
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of β-Aminoenones via Cross-Coupling of In-Situ-Generated Isocyanides with 1,3-Dicarbonyl Compounds

Abstract: An efficient and practical strategy for the synthesis of β-aminoenones from a three-component reaction was developed. Ethyl bromodifluoroacetate serves as a C1 source in this strategy, forming isocyanides in situ with primary amines. This reaction represents the first example of utilization of readily available starting materials to generate isocyanides in situ and sequentially fully converted to β-aminoenones, avoiding the generation of byproduct imines and overinsertion products. The mechanism study suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 64 publications
0
17
1
Order By: Relevance
“…The trace amount of the desired product 3a was observed when benzimidazole was added into the reaction system as a difluorocarbene scavenger; instead, 1-(difluoromethyl)-1H-benzo [d]imidazole was detected by GC-MS (Figure 5C). When N-methyl-N-phenylformamide (30) or isocyanobenzene (31) was subjected to the earlier standard reaction conditions with amines, the corresponding target products 3a and 8 were not obtained (Figure 5D), indicating that the compounds 30 and 31 are not intermediates for this transformation, which is in sharp contrast to our previous reports in which isocyanides are the key intermediates for those transformations with BrCF 2 COOEt (Ma et al, 2018c(Ma et al, , 2018d. To thoroughly understand the reaction sequence, two more control experiments were carried out, in which the primary amine and the secondary amine were added to the reaction mixture stepwise instead of one-pot to check which one is the first amine species interacting with ClCF 2 H. It turned out that primary amine might react with ClCF 2 H before the secondary one since 47% of the desired product was obtained in the primary-secondary amine sequence, whereas no desired product was detected with the secondary-primary amine sequence (Figures 5E and 5F).…”
Section: Mechanism Investigationcontrasting
confidence: 80%
See 1 more Smart Citation
“…The trace amount of the desired product 3a was observed when benzimidazole was added into the reaction system as a difluorocarbene scavenger; instead, 1-(difluoromethyl)-1H-benzo [d]imidazole was detected by GC-MS (Figure 5C). When N-methyl-N-phenylformamide (30) or isocyanobenzene (31) was subjected to the earlier standard reaction conditions with amines, the corresponding target products 3a and 8 were not obtained (Figure 5D), indicating that the compounds 30 and 31 are not intermediates for this transformation, which is in sharp contrast to our previous reports in which isocyanides are the key intermediates for those transformations with BrCF 2 COOEt (Ma et al, 2018c(Ma et al, , 2018d. To thoroughly understand the reaction sequence, two more control experiments were carried out, in which the primary amine and the secondary amine were added to the reaction mixture stepwise instead of one-pot to check which one is the first amine species interacting with ClCF 2 H. It turned out that primary amine might react with ClCF 2 H before the secondary one since 47% of the desired product was obtained in the primary-secondary amine sequence, whereas no desired product was detected with the secondary-primary amine sequence (Figures 5E and 5F).…”
Section: Mechanism Investigationcontrasting
confidence: 80%
“…Our design is based on our recent discovery in which ethyl bromodifluoroacetate (BrCF 2 COOEt) (Ma et al., 2018b, Deng et al., 2019) could act as a C1 source and formylating reagent with amines via quadruple cleavage under basic conditions (Ma et al., 2018a, Ma et al., 2018c, Ma et al., 2018d); we postulated that the quadruple cleavage of ClCF 2 H could also be occurred under the similar sets since it is known that difluorocarbene could be readily accessible from ClCF 2 H under basic conditions. Moreover, compared with BrCF 2 COOEt, ClCF 2 H is obviously much cheaper and more atomic economical.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the reaction pathway, it is not clear yet. However, based on the above experimental results and literatures, [ 24‐31 ] difluoromethylene carbene was involved as the key intermediate.…”
Section: Resultsmentioning
confidence: 73%
“…How to efficiently convert it into refined products is an important scientific problem. There are already very good methods to convert it into an ester, [ 25 ] a monofluoride reagent, [ 26 ] a carbon group, [ 27 ] a α‐bromide, [ 28 ] a carbonyl group, [ 29 ] etc . (Scheme 1).…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Recently, we have found that difluorocarbene can be captured by amines and served as a C1 synthon to synthesize isocyanides, 30 formamides [31][32] and various nitrogen-containing heterocycles [33][34][35][36][37][38][39] (Fig. 1B).…”
Section: Introductionmentioning
confidence: 99%